Descriptive analysis of medium and long-run performance of IPOs: case of firms funded by private equity in Morocco - BELQASMI , Sabrine (Revue Internationale du Chercheur, 2021)
Private equity is a relatively recent activity in Morocco, which is really developed since the 2000s to establish itself today as a source of financing for SMEs, and the IPO is one methods of exiting capital investors, it is therefore interesting to study the impact of capital investors presence in these firms on their stock market performance. This paper examines the long-run stock market performance of Moroccan Initial Public Offerings (IPOs) between 2000 and 2018 on a sample of 13 funded firms listed in Casablanca stock market, using the cumulative abnormal returns (CAR) and the buy-and-hold returns (BHAR) methods, besides an hybrid method based on the MTB ratio. Our findings show a stock market underperformance of firms over the 36 to 60 months of quotation.